The double life of Pocahontas - Fritz, Jean.; Young, Ed (New York : Putnam, 1983)
A biography of the famous American Indian princess, emphasizing her life-long adulation of John Smith and the roles she played in two very different cultures.
Includes index.
Bibliography: p. 92-94.
Keywords: Pocahontas, -- d. 1617 -- Juvenile literature; Pocahontas, -- d. 1617.; Smith, John, -- 1580-1631.; Powhatan, -- ca. 1550-1618.; Indian women -- Virginia -- Jamestown -- Biography -- Juvenile literature; Powhatan women -- Biography -- Juvenile literature; Indians of North America -- Biography; Women -- Biography; Jamestown (Va.) -- History -- Juvenile literature; Virginia -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; Jamestown (Va.) -- History; Virginia -- History -- Colonial period, ca. 1600-1775.